Environmental policy and firm selection in the open economy - Udo Kreickemeier; Philipp M. Richter (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2019)
In this paper, we analyse the effects of a unilateral change in an emissions tax in a model of international trade with heterogeneous firms. We find a positive effect of tighter environmental policy on average productivity in the reforming country through reallocation of labour towards exporting firms. Domestic aggregate emissions fall, due to both a scale and a technique effect, but we show that the reduction in emissions following the tax increase is smaller than in autarky. Moreover, general equilibrium effects through changes in the foreign wage rate lead to a reduction in foreign emissions and, hence, to negative emissions leakage in case of transboundary pollution.
urn:nbn:de:bsz:14-qucosa2-343786
Keywords: F18; F12; F15; Q58; 330; Strategic Environmental Policy; Firm Location; Carbon Leakage; General Equilibrium; Trade and environment; Heterogeneous firms; Unilateral environmental policy; Emissions leakage